Faktor-Faktor yang mempengaruhi Minat Wakaf Masyarakat di Kota Lhokseumawe - Falahuddin Falahuddin; Fuadi Fuadi; Muhammad Rizki Ramadhan (Jurnal EMT KITA, 2019)
This research is to find out the factors that influence the community Waqf Interest in Lhokseumawe City. The data used are primary data with a sample of 100 respondents. The data analysis method uses multiple linear regression with OLS (Ordinary Least Square) method. The results showed that community religious knowledge had a positive and not significant effect on waqf interest in Lhokseumawe. Perception of Waqf has a positive and insignificant effect on community Waqf Interest in Lhokseumawe City, and Revenue has a positive and insignificant effect on Waqf Community Interest in Lhokseumawe City. The determination test results used were 4%.